2004
DOI: 10.1111/j.1365-2885.2004.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and subcutaneous pharmacokinetics of florfenicol in sheep

Abstract: Pharmacokinetic parameters of florfenicol were determined in 10 adult sheep (five wethers and five ewes) after a single 40 mg/kg intravenous (i.v.) dose, and three daily subcutaneous (s.c.) doses of 40 mg/kg of a commercial preparation (Nuflor((R))). The concentration of florfenicol in serum samples was assayed using a proprietary HPLC assay method, and pharmacokinetic parameters derived for individual animal data by each route using compartmental and noncompartmental approaches. Two animals (one male and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
21
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 8 publications
9
21
2
Order By: Relevance
“…in dogs were best fitted to a two compartment open model. These results are in agreement with the findings of previous studies on florfenicol performed in sheep (Ali et al 2003;Lane et al 2004), goats (Atef et al 2001;Ali et al 2003), calves (Varma et al 1986;Adams et al 1987;Decraene et al 1997) and broiler chickens (Shen et al 2003). However, Lobell et al (1994), Soback et al (1995) and Jianzhong et al (2004) found that the disappearance of florfenicol from the plasma after i.v.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…in dogs were best fitted to a two compartment open model. These results are in agreement with the findings of previous studies on florfenicol performed in sheep (Ali et al 2003;Lane et al 2004), goats (Atef et al 2001;Ali et al 2003), calves (Varma et al 1986;Adams et al 1987;Decraene et al 1997) and broiler chickens (Shen et al 2003). However, Lobell et al (1994), Soback et al (1995) and Jianzhong et al (2004) found that the disappearance of florfenicol from the plasma after i.v.…”
Section: Discussionsupporting
confidence: 91%
“…injection of florfenicol, the elimination half-life (t ½b ) of the drug in the plasma of dogs was calculated in the present study to be 3.09 h. This finding was in agreement with the time of 3.2 h reported in cattle (Bretzlaff et al1987), 2.87-3.18 h in calves (Varma et al 1986;Adams et al 1987;Decraene et al 1997), 2.61 h in goats (Atef et al 2001) and 3.02 h in broiler chickens (Shen et al 2003). However, this value (3.09 h) was also much longer than those reported in several previous studies: 1.1 h in dogs (Park et al 2008), 1.49 h in camels (Ali et al 2003), 1.31-1.09 h in sheep (Ali et al 2003;Lane et al 2004), 1.80 h in equines (McKellar and Varma 1996) and 1.54-0.90 h in rabbits (Abd El- Aty et al 2004;Park et al 2007). Differences in kinetic parameters are relatively common, and frequently related to interspecies variation, age, breed, health status of the animals and/or the assay method used.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…respectively (9,13). Another study in sheep in 2004 found Vd=0.55L/Kg (14). These Vds could indicate a good milk excretion.…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC and extraction procedures were modified from previously published methods [24,25]. The HPLC system consisted of a pump (LC-10A DVP) with UV-vis detector (SPD-10 AVP), auto injector (SIL-10A DVP), solvent degasser (DGV-12 A) and Shimadzu class-VP software (Ver 6.12 SP4) (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%